Challenges in Contract Theory: Performance-Based Pay as a Solution to Address Promotion Risk in a Competitive Corporate Environment - Ria Wulandari; Yuni Sara (LPPM STIE Kasih Bangsa, 2025)
This study examines the challenges in implementing contract theory, particularly related to corporate performance pay as a solution to promotion risk in a competitive environment. Performance-based pay serves to increase employee motivation and reduce uncertainty in promotion, but has the potential to create unhealthy competition and reduce teamwork. This study suggests that a balanced incentive contract design, which combines financial and non-financial rewards, can optimize individual performance without sacrificing team harmony. Although performance-based pay can provide short-term benefits, it is important for companies to consider its long-term impact on employee satisfaction and collaboration within the organization. This study provides theoretical and practical insights for companies in designing fair and effective promotion systems